Utilization of polyethylene sleeves with forced aeration for composting of broiler carcasses on mass depopulation events: Laboratory-scale simulations and sensitivity analyses. (1st January 2023) - Avidov, Ran; Lublin, Avishai; Sudharsan Varma, Vempalli; Saadi, Ibrahim; Yoselewitz, Israel; Chen, Yona; Laor, Yael
Graphical abstract: Highlights: Composting broiler carcasses and litter is feasible during mass depopulation events. After 30 days of composting, Newcastle and Avian flu were reduced below detection. Salmonella survived composting at 40 °C both under aerobic and anaerobic conditions. Biomass losses was substantially higher under aerobic and mesophilic conditions. Wet culling methods can lead to issues of excess water within composting sleeves. Abstract: Composting poultry carcasses and the infected litter is considered feasible during mass depopulation events in response to disease outbreaks. We demonstrate the effect of temperature (40, 50, 60 °C) and aerobic/anaerobic conditions on the degradation of broiler carcasses and broiler litter (BL) and the elimination of pre-inoculated Avian flu and Newcastle viruses and Salmonella  Infantis (3.3 × 10 5.6 EID50, 7 × 10 6.0 EID50 and 2 × 10 7 CFU g-dry matter (DM) −1, respectively). Six broiler carcasses and BL were inoculated and treated with a water-based foam, simulating a common culling method. After 30 days of composting, both viruses were eliminated under all conditions, while  Salmonella  persisted at 40 °C under aerobic and anaerobic conditions (7.4 × 10 5  and 4.4 × 10 3  CFU g-DM −1, respectively). Mass losses were 42–44, 24–26, and 18–22% (aerobic) and 18–27, 21–23, and 0–7% (anaerobic) at 40, 50, and 60 °C, respectively. In the end, the associated odors were not typical of carcasses (aerobic), or they were strong and offensive (anaerobic). Considering the observed mass losses and biomass water holding capacity, we present a sensitivity analysis of the water balance expected in composting sleeves if they are utilized on mass depopulation events. Composting of the carcasses and the BL in enclosed sleeves with forced aeration, following culling by means of water-based foam will generate excess water, depending on sleeve volumes, aeration conditions, and co-addition of absorbing materials like sawdust. No excessive moisture is expected if dry culling methods are used.